2018
DOI: 10.17650/1994-4098-2018-14-2-76-81
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiles of Endometrial Hyperplasia and Endometrial Intraepithelial Neoplasia

Abstract: Objective: to assess molecular profiles of endometrial hyperplasia and endometrial intraepithelial neoplasia.Materials and methods. We conducted a retrospective study that included 77 patients with a morphologically verified hyperplastic process in the endometrium. Of them, 34 patients had endometrial hyperplasia and 33 patients had endometrial intraepithelial neoplasia. The control group comprised 30 women with no endometrial disorders according to the results of histological examination.Results. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The results of our work contradict the data that in normal endometrium the synthesis of VEGF is stimulated by the influence of estradiol, in neoplasia this effect worsens or disappears. Although researchers have studied a highly significant negative relationship between VEGF and progesterone receptor concentrations in endometrial hyperplasia, there is no correlation between VEGF and progesterone receptor expression [2,3,9]. However, it should be borne in mind that the etiopathogenetic mechanisms of development of endometrial tissue malignancy are not definitively established, the influence of hormonal factors exists, but it is not always associated with cancer risks, because in our work were more active processes in the postmenopausal period.…”
Section: Fig 2 Expression Of Vegf In Endometrial Cells In Different Pathological Conditions In Different Age Categories (Ru)mentioning
confidence: 74%
See 4 more Smart Citations
“…The results of our work contradict the data that in normal endometrium the synthesis of VEGF is stimulated by the influence of estradiol, in neoplasia this effect worsens or disappears. Although researchers have studied a highly significant negative relationship between VEGF and progesterone receptor concentrations in endometrial hyperplasia, there is no correlation between VEGF and progesterone receptor expression [2,3,9]. However, it should be borne in mind that the etiopathogenetic mechanisms of development of endometrial tissue malignancy are not definitively established, the influence of hormonal factors exists, but it is not always associated with cancer risks, because in our work were more active processes in the postmenopausal period.…”
Section: Fig 2 Expression Of Vegf In Endometrial Cells In Different Pathological Conditions In Different Age Categories (Ru)mentioning
confidence: 74%
“…A clear tendency to increase the prevalence of hormone-dependent diseases related to preproliferative processes and endometrial cancer are observed against the background of increasing their incidence and rejuvenation of the age of manifestation [1,3,13]. Unspecified information about the etiopathogenesis of hyperplastic processes limits the possibilities of therapeutic treatment and obtaining positive results.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations